Long‐term efficacy of add‐on lacosamide treatment in children and adolescents with refractory epilepsies: A single‐center observational study. (17th April 2018) - Rosati, Anna; Ilvento, Lucrezia; Rizzi, Riccardo; Doccini, Viola; Leo, Maria Carmela; Pugi, Alessandra; De Masi, Salvatore; Guerrini, Renzo
Summary: Objective: To assess long‐term efficacy and tolerability of lacosamide (LCM) as adjunctive treatment through a retrospective study in children and adolescents with refractory epilepsies. Methods: All patients consecutively treated with LCM as add‐on for refractory focal and generalized epilepsy and followed at the Neuroscience Center of Excellence of the Meyer Children's Hospital of Florence between January 2011 and September 2015 were included in the study. Responder rate, relapse‐free survival, and retention rate were calculated. Tolerability was assessed by reporting adverse events. Results: A total of 88 individuals (41 female) aged 4 months to 18 years (median 10.5 years; mean ± SD 10.6 ± 4.8 years) received add‐on LCM treatment for refractory epilepsy. Thirty‐four patients (38.6%) were responders with a median time to relapse of 48 months. Nine (26.4%) of the 34 responders were seizure‐free. For all 88 patients, the probability of remaining on LCM without additional therapy was 74.4% at 6 months, 47.7% at 12 months, 27.9% at 24 months, 18.0% at 48 months, and 8.2% at 72 months of follow‐up. No statistically significant differences in relapse and retention time were observed with regard to epilepsy and seizure types, duration and course of epilepsy, number and type of antiepileptic drugs (AEDs; sodium channel blockers vs others) used in add‐on. The most frequent adverse events were dermatological (4/11) and behavioral (3/11). Significance: This study documents a real‐world progressive and significant loss of LCM efficacy over time in a pediatric population. Further prospective studies on larger populations are required to confirm the remarkable loss of LCM efficacy over time.